Use of weight-for-age-data to optimize tablet strength and dosing regimens for a new fixed-dose artesunate-amodiaquine combination for treating falciparum malaria - Walter RJ Taylor; Dianne J Terlouw; Piero L Olliaro; Nicholas J White; Philippe Brasseur; Feiko O ter Kuile
OBJECTIVE: To test a novel methodology to define age-based dosing regimens for the treatment of malaria with a new, user-friendly, blister-packaged fixed-dose combination of artesunate and amodiaquine. METHODS: A weight-for-age reference database of 88 054 individuals from sub-Saharan Africa was compiled using data from Demographic Health Surveys, observational and intervention studies, and standardized for sex, age and malaria risk. We then determined the optimal tablet strength (milligram (mg) per tablet) and age-dose categories for the combination of artesunate and amodiaquine. The proportions of patients predicted to receive doses within newly defined therapeutic ranges for amodiaquine (7-15 mg/kg/day) and artesunate (2-10 mg/kg/day), were estimated for different age categories and mg tablet strengths using models based on the weight-for-age reference database. FINDINGS: The optimal paediatric (p) and adult (a) strength tablets contained 25/67.5 and 100/270 mg artesunate/amodiaquine, respectively. A regimen with five age categories: 0-1 months (½ p), 2-11 months (1 p), 1-5 years (2 p), 6-13 years (1 a), and > 14 years (2 a) had an overall dosing accuracy of 83.4% and 99.9% for amodiaquine and artesunate, respectively. CONCLUSION: The proposed method to use weight-for-age reference data from countries where malaria is endemic is a useful tool for designing age-based dosing regimens for antimalarial drugs for drug registration and field use.